Comparing Treatment Outcomes in Children and Adolescents With ADHD to Other Disorders Within an Australian and Dutch Outpatient Cohort. Issue 14 (December 2022) - Payne, Leanne; Roest, Sanna L.; Lu, Zhen Qi; Zendarski, Nardia; Bisset, Matthew; Sciberras, Emma; Stathis, Stephen; Siebelink, Bart M.; Vermeiren, Robert R. J. M.; Bellgrove, Mark A.; Coghill, David; Middeldorp, Christel M.
Objective: Previous studies at child and youth mental health services (CYMHS) suggest that children with ADHD have poorer outcomes compared to those with other diagnoses. This study investigates this in more detail. Methods: Children with ADHD were compared to those with ASD and those with emotional disorders, on routinely collected outcomes at CYMHS in Australia ( N = 2, 513) and the Netherlands ( N = 844). Results: Where the emotional disorders group reached a similar level of emotional symptoms at the end-of-treatment as the ADHD and ASD groups, the latter two groups still had higher scores on ADHD and ASD symptoms (attention and peer problems). The poorer outcomes were mainly explained by higher severity at baseline. In Australia, an ADHD and/or ASD diagnosis also independently contributed to worse outcomes. Conclusion: Those with neurodevelopmental disorders within both countries had poorer outcomes than those with emotional disorders. Services should aim to optimize treatment to ensure best possible outcomes.